- REVIEW ARTIKEL: Penyembuhan Luka Insisi Sediaan Topikal dari Tanaman Herbal: - - Agung Fajarningrum, Putu Yunda (Jurnal Jejaring Matematika dan Sains, 2022)
An incision wound is a wound made using a scalpel to open deeper tissues or organs, taking into account the size, location, and purpose of the wound. Many herbal plants have been reported to have wound healing activity and can be used as alternative therapies. This review aims to determine the potential of plants that have wound healing activity which is focused on studying herbal plants that have wound healing activity in vivo. The results of the study from 30 articles that plants that have wound healing activity are Dewa leaves, gotu kola leaves, tiger grass, jatropha, binahong leaves, earrings leaves, red betel leaves, african leaves, aloe vera leaves, jasmine leaves, kecombrang flowers, jengkol leaves, meniran leaves, broken bones, betadine leaves, kenikir leaves, Java wood stems, bitter melon leaves, Indian almond leaves. Herbal plant preparations of ethanol extract gel from red castor leaves (Jatropha gossypifolia Linn) gave the optimum effect in wound healing in rabbits at a concentration of 3%.